Climate Protection in the German Electricity Market: Opportunities for Coal Technologies through CO₂ Capture and Storage? - Claudia Kemfert; Katja Schumacher (Weekly Report, 2005)
The German electricity market is facing two major challenges: competition and climate protection. The liberalization of the electricity sector in Europe following the directive on the single internal market is increasing competition between suppliers of electricity, while the trading in emissions certificates, which started in January 2005, aims at reducing emission of carbon dioxide. This gives a competitive advantage to electricity suppliers who can produce cost-efficiently while protecting the environment and the climate. As conventional power stations retire and have to be shut down there will be a need for major replacement of generation capacities in the next two decades. In the longer term a technology that enables CO2 to be captured and stored could enable electricity to be generated from coal without damage to the climate. If emissions certificates cost more than 30 euros per tonne of carbon dioxide electricity generation both in coal-fired power stations with CO2 capture and storage (CCS) and from renewable energy sources - especially in more advanced wind power plants - could become economical. Hence the development of both these technologies is important to secure future energy supplies.
Keywords: 330